Shockwave lithotripsy for kidney stones as a first-line therapy in children younger than 2 years. Issue 2 (April 2020) - Asi, Tariq; Dogan, Hasan Serkan; Altan, Mesut; Bozaci, Ali Cansu; Ceylan, Taner; Asci, Ahmet; Tekgul, Serdar
Summary: Background: The incidence of urolithiasis in children has risen worldwide over the last decades with geographical varieties. As pediatric patients begin forming stones earlier in life, they have high risk of recurrence. Extracorporeal shockwave lithotripsy (SWL) is a non-invasive treatment modality that is preferred in the management of pediatric stones. Reports about the safety and efficacy of SWL in patients younger than 24 months are scarce in the literature. Objective: The aim of the study was to evaluate the effectiveness and safety of SWL in patients younger than 24 months. The authors also aimed to assess the validity of the Dogan nomogram in predicting stone-free rates. Study design: Between January 2009 and March 2019, data of 247 patients younger than 24 months at the time of SWL were retrospectively collected. Analysis was performed on 260 renal units. Success was considered in patients who were completely free of stones after the first session. Results and Discussion: The female/male ratio was 103/157, with a median age of 15 (5–24) months, a median stone size of 8 (3–30) mm and a median follow-up period of 7 (3–20) months. Multiple stones and lower calyx stones were observed in 19.6% (51/260) and 23.4% (61/260) of patients, respectively. Complications were detected in 5.8% (15/260) of patients (9 with steinstrasse, 3 with UTI, 2 with vomiting, 1 with hematuria). After the first session, 56.9% (148/260) of patients were stone-free. Forty-six of the failed 112 first sessions underwent second session. A total of 5 patients had a third session. The efficacy quotient was 57%. On univariate analysis, younger age (≤16 months), single stone, small stone size (<10 mm), and non–lower pole location were significant predictors of stone clearance. On multivariate analysis, younger age (=<16 months) and single stone remained significant. The Dogan nomogram score lower than 150 was found to be a good cutoff point to predict better stone clearance (Table). Conclusion: Shockwave lithotripsy is a safe and effective treatment modality in patients younger than 24 months and could be the first option in this particular age-group in whom the other endourological modalities are not always applicable. The Dogan nomogram is reliable in predicting the stone-free rate in this age-group. Table Comparative analysis of the factors affecting the stone-free rates after a single session. Table S Parameter Stone-free (SF) rate (%) P Gender Male 61.1% 0.090 Female 50.5% Metabolic abnormality None 64.5% 0.198 Hypocitraturia 58.8% Hyperoxaluria 42.1% Hypocitraturia + hyperoxaluria 73.1%% Degree of hydronephrosis None, mild 56.5% 0.750 Moderate, severe 59.1% Age (months) ≤16 64.3% 0.003 >16 45.6% Side Right 52.4% 0.152 Left 61.2% Stone number Single 64.6% <0.001 Multiple 25.5% Size ≤10 mm 61.3% 0.007 >10 mm 41.1% Location Lower pole calyx 47.2% 0.051 Non–lower pole 60.6% Previous intervention Yes 58.0% 0.864 No 56.7% Dogan nomogram score ≤150 64.9% <0.001 >150 27.3%